A Review of the Catalytic Effects of Lead‐Based Ballistic Modifiers on the Combustion Chemistry of Double Base Propellants. Issue 1 (4th October 2020) - Warren, Lisette R.; Wang, Zixuan; Pulham, Colin R.; Morrison, Carole A.
Abstract: Lead‐based compounds are the current industry‐standard ballistic modifier for double‐base propellants, but there is a pressing need for alternatives as incoming European legislation will soon ban their use. This review article introduces the main concepts and terminologies in the combustion chemistry of double‐base propellants, and critically evaluates the four theories put forward in the literature to account for the ballistic modifier effect, namely (i) photochemical, (ii) chelating/complex, (iii) carbon soot, and (iv) free radical theories. We also review the literature on current trends in ballistic modifier research and note the emerging potential of oxide nanoparticles (in particular Bi2 WO6 ) and Cu/Bi encapsulated in carbon nanotubes as lead‐free ballistic modifier additives. Abstract :